The Impact of Technological Innovation on Sustainability and Competitiveness in the Food and Beverage Industry Sector - Muhamad Teguh Setiadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
Technological innovation has become a key element in supporting sustainability and increasing the competitiveness of the food and beverage industry. This study analyzes the impact of implementing technological innovation, such as automation, supply chain digitalization, and environmentally friendly technology, on operational sustainability and increasing company competitiveness. This study uses a descriptive quantitative approach with a population of 100 companies in Indonesia's food and beverage sector. The results show that 75% of companies have adopted at least one form of technological innovation, with production automation (40%) and supply chain digitalization (35%) as the most commonly implemented technologies. Implementing these technologies contributes to increased operational efficiency, reduced costs, and strengthened competitive positions in the global market. In addition, environmentally friendly innovations, such as using renewable raw materials and biodegradable packaging, improve the company's reputation in the eyes of consumers who are increasingly concerned about the environment. The regression results show a significant relationship between the implementation of technological innovation and sustainability, where companies that adopt green technology report a decrease in carbon emissions of up to 20% in the last five years. This study concludes that companies that are proactive in embracing technological innovation have a more significant competitive advantage and the ability to meet market demands and sustainability regulations. More robust policy support is needed to help small and medium enterprises access advanced technologies to ensure sustainable industrial growth.